Pengaruh Corporate Sosial Responsibility (CSR) dan Struktur Modal Terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Moderating: Studi pada Perusahaan Sektor Consumer Non-Cyclicals yang Terdaftar di BEI Periode Tahun 2020-2023 - Monica Sandra Dewi; Sri Sudarsi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) and capital structure on firm value, as well as the role of profitability as a moderating variable. The object of this study is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. The population of this study amounted to 125 companies, and those that met the sample criteria included 49 non-cyclical consumer sector companies. The firm value in this study was proxied by the Price to Book Ratio (PBV) ratio. The analysis method used was multiple linear regression with the help of SPSS software. The results of the study prove that CSR has no effect on firm value. On the contrary, capital structure has an effect on firm value. In addition, the role of profitability as a moderating variable has not been able to moderate the relationship between CSR and firm value, meaning that profitability does not strengthen or weaken the relationship. However, profitability has been shown to moderate the relationship between capital structure and firm value, which is precisely profitability weakens the relationship. This indicates that for companies that have a high level of profitability, increasing debt in the capital structure significantly reduces the value of the company.